Impact of Human Papillomavirus Vaccination on Male Disease: A Systematic Review - Catarina Rosado; Ângela Rita Fernandes; Acácio Gonçalves Rodrigues; Carmen Lisboa (Vaccines, 2023)
Human papillomavirus (HPV)-related diseases are highly prevalent in men worldwide, comprising external anogenital condyloma, anal intraepithelial neoplasia (AIN), penile intraepithelial neoplasia (PIN), and anogenital and oropharyngeal cancers. There is exceptionally low vaccine coverage in the male population. Only 4% of men were fully vaccinated, worldwide, as of 2019. The aim of this review is to assess the impact of HPV vaccination on male disease. Three databases (MEDLINE, Web of Science, Scopus) and Clinical Trials.gov were searched. We included thirteen studies, eight randomized controlled trials (RCTs), and five cohorts, comprising a total of 14,239 participants. Regarding anal disease, seven studies reported HPV vaccine efficacy ranging from 91.1% to 93.1% against AIN1, and ranging from 89.6% to 91.7% against AIN2|3 and anal cancer. Five studies showed an efficacy against genital condyloma of 89.9% in HPV-naïve males, varying between 66.7% and 67.2% in intention-to-treat populations. Studies reporting no efficacy have included older participants. These results support vaccination of young men previously infected, beyond HPV-naïve males. The evidence quality was moderate to low for most outcomes, namely genital diseases. RCTs are needed to assess the efficacy of HPV vaccination on male oropharyngeal cancer.